1977
DOI: 10.1038/bjc.1977.115
|View full text |Cite
|
Sign up to set email alerts
|

C-type and intracisternal A-type virus particles during epidermal carcinogenesis by tobacco smoke condensate in BALB/c mice

Abstract: Summary.-Electron microscopic observations of sequential stages of skin carcinogenesis induced by tobacco smoke condensate (SC) and a cyclohexane fraction of tobacco smoke condensate (G) revealed an increase in incidence of intracisternal A particles within the epidermal cells. Tumours induced by SC also contained C-type particles, but these were not seen in G-induced tumours or after irritant or solvent treatment. There was no evidence of an increase in intracisternal A particles after irritant or solvent tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Similar observations were made in BALB/c mouse skin tumours induced by polycyclic hydrocarbon treatment (Bibby & Smith, 1975). A further study (Bibby & Smith, 1977b) has revealed the presence of C-type viruses budding from cell membranes in squamous cell carcinomas induced in BALB/c mouse skin by painting with tobacco smoke condensate. These results suggest a possible activation of an RNA oncogenic virus by chemical carcinogens.…”
mentioning
confidence: 99%
“…Similar observations were made in BALB/c mouse skin tumours induced by polycyclic hydrocarbon treatment (Bibby & Smith, 1975). A further study (Bibby & Smith, 1977b) has revealed the presence of C-type viruses budding from cell membranes in squamous cell carcinomas induced in BALB/c mouse skin by painting with tobacco smoke condensate. These results suggest a possible activation of an RNA oncogenic virus by chemical carcinogens.…”
mentioning
confidence: 99%